Assessing the Motivation of Civil Servant in Providing Public Services in Higher Education - Rivai, Andi Muhammad; S., Muh. Rizal; Baharuddin, Aris; Bakhtiar, Bakhtiar (Universitas Negeri Makassar, 2021)
Abstract. This study aims to examine how the motivation of academic services for educators and education personnel in higher education. The findings of this study are expected to become recommendations in developing programs or forms of evaluation aimed at improving the performance and motivation of academic services for teaching staff and teaching staff in tertiary institutions. This research is a survey research which aims to determine the general description of the motivation for academic services for teaching staff and teaching staff at state universities. Based on the research findings obtained, it can be concluded that from the 4 dimensions of motivation for public services, the first dimension, namely the interest in making public policy, is the dimension least owned or implemented by the research respondents. While the other three dimensions can be said to be in the high category in the sense that the respondents already have and have implemented these three dimensions in the delivery of public services. Based on these data, it can be concluded that the lack of motivation for academic services by the state civil servants tends to be due to their lack of interest in public policy making. Keywords: Public Service, Public Service Motivation, Civil Servant, Academic Affairs Public Service